Novax or Novak? Estimating Social Media Stance towards Celebrity Vaccine Hesitancy (Student Abstract) - Hota, Madhav; Khorramrouz, Adel; KhudaBukhsh, Ashiqur R. (Proceedings of the AAAI Conference on Artificial Intelligence, 2024)
On 15 January 2022, noted tennis player Novak Djokovic was deported from Australia due to his unvaccinated status for the COVID-19 vaccine. This paper presents a stance classifier and evaluates public reaction to this episode and the impact of this behavior on social media discourse on YouTube. We observed a significant spike of individuals who supported and opposed his behavior at the time of the episode. Supporters outnumbered those who opposed this behavior by over 4x. Our study reports a disturbing trend that following every major Djokovic win, even now, vaccine skeptics often conflate his tennis success as a fitting reply to vaccine mandates.